Análisis de la información periodística sobre la pugna entre el CNE y Yasunidos. - Burbano Urresta, Lissette Stefanía (2016)
This research focuses on discourse analysis of the press coverage about the conflict between Yasunidos and CNE, as in the digital versions of two Ecuadorian daily El Universo and The Telegraph, published in the months of April, May and June 2014, when the which projects the problem. This work aims to establish whether there are biases in the press coverage of this issue in particular, whether these media show or not show any kind of politicization in presenting the news or whether they are always given by the standards of journalistic quality. It should be clarified that it is not bumping issues concerning Ecuadorian politics itself, but rather as his principle point discourse analysis that handle these daily, because based on the defense of their interests have been promoting a biased way information consciously or unconsciously by the journalist, and finally it comes to influence the reader.